HEPATIC FASCIOLIASIS - JATCHAVALA, Janjira; PEKANAN, Patchrin; PONGCHAIRUEK, Paisal; JAOVISIDHA, Suphaneewan (The ASEAN Journal of Radiology, 2023)
A case of hepatic fascioliasis without peripheral eosinophilia is presented. CT scan revealed a cluster of small abscesses in subhepatic area of the liver with tract like fashion. The adjacent subhepatic cyst was noted as a complication of the disease.